PENGARUH KOMPRES DAUN KOL TERHADAP PEMBENGKAKAN PAYUDARA PADA IBU POST PARTUM DI RUMAH SAKIT SUKMA WIJAYA SAMPANG - Lestari Ika Widyyati, Mei; Ramadhanti, Vinnika Kamaisya; Istibsaroh, Faridatul; Jatimi, Atika; Amilia, Yunita (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Breast engorgement occurs when breast milk is clogged due to the narrowing of the milk ducts or because the mammary glands do not empty. Severe breast engorgement can cause discomfort to the mother because it can cause pain, interfere with the baby's ability to breastfeed, and even cause mastitis and breast abscesses in the mother. Objective: To determine the effect of cabbage leaf compresses on breast swelling in postpartum mothers at Sukma Wijaya Hospital, Sampang. Method: The research design used in this research is a pre-experimental design with one group pretest-posttest. The population in this study was 46 postpartum mothers at Sukma Wijaya Sampang Hospital using a probability sampling technique, namely simple random sampling. The instrument used in this study used a checklist, namely a direct assessment of the incidence of breast swelling using the Six Point Engorgement Scale (SPES). The results of this research were processed using the Wilcoxon test, the results are presented in the form of tables and narratives. Result: The results of this study showed that the majority of respondents before the intervention showed moderate pain on a scale of 4-5, namely 24 respondents (57.1%) and almost all respondents after the intervention showed mild pain on a scale of 2-3, 33 respondents (78 .6%). The results of the Wilcoxon Test statistical test obtained a p-value of 0.000 < a = 0.05. So it can be concluded that there is an effect of cabbage leaf compresses on breast swelling in post-partum mothers at Sukma Wijaya Hospital, Sampang. Conclusion: Cabbage leaf compress is an alternative that can be used to treat breast swelling. Cabbage leaf compresses are effective in reducing breast swelling compared to not giving cabbage leaf compresses.